Effects of subsurface drip irrigation and nitrogen fertilizer management on N2O emissions and forage yield in alfalfa production - Ma, Hongxiu; Sun, Quan; Zhang, Xiaojuan; Jiang, Peng (Frontiers in Plant Science, 2025)
Reducing emissions of the greenhouse gas nitrous oxide (N2O) while improving forage yield and quality is essential for sustainable agriculture in the context of global warming. However, how to reduce N2O emissions through water and nitrogen management in alfalfa planting is still unclear. In this two-year field experiment, the effects of three irrigation rates (W1, 375 mm; W2, 525 mm; W3, 675 mm) and five nitrogen (N) fertilizer application rates (N0, 0 kg N ha−1; N1, 75 kg N ha−1; N2, 150 kg N ha−1; N3, 225 kg N ha−1; N4, 300 kg N ha−1) on alfalfa yield, quality, resource use efficiency, and N2O emissions were explored. The results showed that irrigation combined with N application resulted in greater N2O emissions than irrigation alone. The cumulative N2O emissions increased with the increase of irrigation rate, and the average maximum cumulative N2O emissions of the W3 treatment (0.58 kg ha−1) increased by 94.14% and 57.38% compared with that of the W2 and W1 treatment, respectively. The cumulative N2O emissions also increased with the increase of the N application rate, and the average cumulative N2O emissions of the N4 treatment (0.69 kg ha−1) increased by 31.99%, 62.87%, 108%, and 173% compared with that of the N3, N2, N1, and N0 treatments, respectively. The variation of the average N2O emission coefficient was similar to that of the cumulative N2O emissions, and the W3 treatment (5.46) and N4 treatment (4.84) had the largest coefficients. Yield, crude protein, crop water productivity (WPc), and N2O emissions increased with the increase of N application rate, regardless of irrigation rate, with maxima occurring at N2 or N3 levels. These results suggest that the low NUE may be caused by the high cumulative N2O emissions. Besides, the combination of the irrigation rate 525 mm and the N application rate 150–225 kg N ha-1 could significantly increase alfalfa yield and crude protein content compared to other irrigation and nitrogen application treatments. However, further increasing irrigation and N rates failed to obtain further yield and crude protein increases, but led to N2O emission increase and WPc and NUE reductions. This may cause serious resource waste and environmental pollution.